2019
DOI: 10.3390/pharmaceutics11060261
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anti-Angiogenic Effects Using Peptide-Based Combinatorial Delivery of siRNAs Targeting VEGFA, VEGFR1, and Endoglin Genes

Abstract: Angiogenesis is a process of new blood vessel formation, which plays a significant role in carcinogenesis and the development of diseases associated with pathological neovascularization. An important role in the regulation of angiogenesis belongs to several key pathways such as VEGF-pathways, TGF-β-pathways, and some others. Introduction of small interfering RNA (siRNA) against genes of pro-angogenic factors is a promising strategy for the therapeutic suppression of angiogenesis. These siRNA molecules need to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…According to the results in Figure 10 b, VEGFA gene expression was decreased by RGD1-mediated anti-VEGFA siRNA delivery by 28.74% and 41.9%, respectively. Previously, we have shown that similar silencing of VEGFA gene expression resulted in significant anti-angiogenic effects in endothelial cell modeland in rat model of endometriosis [ 44 , 46 ]. Thus, RGD1-polyplexes can be suggested as siRNA-carriers in anti-angiogenic therapeutic RNAi.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results in Figure 10 b, VEGFA gene expression was decreased by RGD1-mediated anti-VEGFA siRNA delivery by 28.74% and 41.9%, respectively. Previously, we have shown that similar silencing of VEGFA gene expression resulted in significant anti-angiogenic effects in endothelial cell modeland in rat model of endometriosis [ 44 , 46 ]. Thus, RGD1-polyplexes can be suggested as siRNA-carriers in anti-angiogenic therapeutic RNAi.…”
Section: Resultsmentioning
confidence: 99%
“…Transfection experiments in EA.hy926 cells were performed in triplicate as previously described [ 46 ]. After incubation in a fully supplemented cell culture medium for 48 h, cells were taken for RNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, delivery of siRNA specifically into endothelial cells is a promising strategy to impair tumor angiogenesis. To this end, a study by Egorova et al [ 69 , 70 ] showed how siRNA-mediated silencing of vascular epithelial growth factor signaling (VEGF-A, VEGFR1) and endoglin, a co-receptor for TGF-β, impaired endothelial cell migration and proliferation. However, an efficient and specific siRNA delivery system is crucial for the development of this promising approach.…”
Section: Sirna Therapeutics Targeting the Tmementioning
confidence: 99%
“…The VEGF–VEGFR axis [ 138 ] plays central roles in angiogenic processes. In order to reduce angiogenetic progression in breast cancer, Egorova et al [ 70 ] used an L1 peptide-based polyplex for the delivery of siRNAs targeting VEGFA, VEGFR1, and endoglin transcripts in CXCR4-positive breast cancer and endothelial cells lines. Polyplexes are polymeric systems in which nucleic acids such as siRNAs are complexed with a cationic polymer through electrostatic interactions [ 139 , 140 ].…”
Section: Sirna Delivery Strategiesmentioning
confidence: 99%
“…They used three types of cationic cholesterol derivatives to investigate an optimal formulation to achieve the best performance in terms of gene-silencing and cellular uptake effects. In Egorova et al, [9] researches on modular peptide carriers for the delivery of siRNAs to therapeutic angiogenesis inhibition were performed. In particular, the transfection properties of siRNA as polyplexes were studied in breast cancer cells and endothelial cells.…”
mentioning
confidence: 99%